Genotype-phenotype correlations, dystonia and disease progression in spinocerebellar ataxia type 14 - Chelban, V; Wiethoff, S; Fabian-Jessing, B; Haridy, N; Khan, A; Efthymiou, S; Becker, E; O'Connor, E; Hersheson, J; Newland, K; Hojland, A; Gregersen, P; et al. (Wiley, 2018)
Spinocerebellar ataxia type 14 is a rare form of autosomal dominant cerebellar ataxia caused by mutations in protein kinase Cγ gene. Clinically, it presents with a slowly progressive, mainly pure cerebellar ataxia.Using next generation sequencing, we screened 194 families with autosomal dominant cerebellar ataxia and normal polyglutamine repeats. In-depth phenotyping was performed using validated clinical rating scales neuroimaging and electrophysiological investigations.We identified 25 individuals from 13 families carrying pathogenic mutations in protein kinase Cγ gene. A total of 10 unique protein kinase Cγ gene mutations have been confirmed of which 5 are novel and 5 were previously described. Our data suggest that the age at onset is highly variable; disease course is slowly progressive and rarely associated with severe disability. However, one third of patients presented with a complex ataxia comprising severe focal and/or task-induced dystonia, peripheral neuropathy, parkinsonism, myoclonus, and pyramidal syndrome. The most complex phenotype is related to a missense mutation in the catalytic domain in exon 11.We present one of the largest genetically confirmed spinocerebellar ataxia type 14 cohorts contributing novel variants and clinical characterisation. We show that although protein kinase Cγ gene mutations present mainly as slowly progressive pure ataxia, more than a third of cases had a complex phenotype. Overall, our case series extends the phenotype and suggests that protein kinase Cγ gene mutations should be considered in patients with slowly progressive autosomal dominant cerebellar ataxia, particularly when myoclonus, dystonia, or mild cognitive impairment are present in the absence of polyglutamine expansion. © 2018 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.